Salt effect on bilayer phase transitions of dipalmitoylphosphatidylglycerol in saline water under high pressure. Issue 2 (3rd April 2019) - Goto, Masaki; Okamoto, Hirotsugu; Tamai, Nobutake; Fukada, Kazuhiro; Matsuki, Hitoshi
ABSTRACT: The phase transitions of dipalmitoylphosphatidylglycerol (DPPG) bilayer membrane at high NaCl concentrations under high pressure were investigated to construct the temperature–pressure phase diagram and to determine phase-transition properties. The constructed phase diagrams exhibited qualitative resemblance to that of the dipalmitoylphosphatidylcholine (DPPC) bilayer membrane: they showed the gel-phase polymorphism including the pressure-induced bilayer interdigitation. The phase-transition properties of the DPPG bilayer membrane changed in a salt concentration-dependent manner. We discussed the salt effect on the DPPG bilayer membrane from the variation in interactions between the polar head groups of the PG molecules.